Penerapan Clinical Supervision untuk Meningkatkan Class Asessment Management bagi Guru Sekolah Dasar Binaan - H Muhsin (Jurnal Paedagogy, 2021)
This study aims to apply clinical supervision to improve the ability of elementary school teachers in conducting class assessments. The method used utilizes three cycles of action research involving 23 teachers from 10 primary schools under the guidance of North Batukliang District, Central Lombok Regency. The data has been collected through the observation of the class assessment ability in each action process. The data analysis technique of this study used quantitative and qualitative descriptive analysis. The results obtained that the first cycle is below the expected completeness percentage (≤85%) which is 67.17%, while in the second cycle it also does not meet the completeness percentage which is 77.17%, and in the third cycle it is 85.86 % (Completed). The study concluded that the implementation of clinical supervision to improve the class assessment ability of elementary school teachers had a significant impact. In the future, these results can be a reference for supervisors in conducting school supervision to improve the competence of other teachers.